PERANCANGAN ALAT BANTU PRESENTASI PEMANDIAN AIR PANAS DAN VILLA PENGINAPAN PROMASAN GREENLAND NGLIMUT GONOHARJO DENGAN METODE AIDA BERBASIS 3D WALKTHROUGH (STUDI KASUS DI PROMASAN GREENLAND NGLIMUT) - Muhammad Rizky Saputra (STEKOM PRESS, 2017)
Promas Greenland Nglimut Is a Hot Spring Bath and Villa Accommodation, Promas Greenland Ngonut Gonoharjo is located at an altitude of 700m above sea level, located in Limbangan District and 30 km from the city of Semarang. The purpose of this study is to introduce to the public so that people are more aware of greenland promas tourism, as well as interested in traveling to greenland promos gonoharjo and increasing marketing of greenland promasan tourism to be able to compete with other tourism in Kendal district. This study uses the Aida method and uses a 3D model. The subject of this research is to the public and tourists who will visit Greenland promasan tourism. The results of this study were able to attract the public or tourists to visit Greenland promising tourist sites and improve their marketing system, the results obtained from marketing with 3D models are able to improve the marketing system that the public will find out the specifications and forms of Greenland promotions before visiting or traveling. This is supported by the existence of good management and adequate facilities so that visitors feel comfortable and happy.